PD‐1 expression affects cytokine production by ILC2 and is influenced by peroxisome proliferator‐activated receptor‐γ. Issue 1 (19th November 2019) - Batyrova, Banu; Luwaert, Fien; Maravelia, Panagiota; Miyabayashi, Yuria; Vashist, Neha; Stark, Julian M.; Soori, Sara Y.; Tibbitt, Christopher A.; Riese, Peggy; Coquet, Jonathan M.; Chambers, Benedict J.
Abstract: Introduction: Innate lymphoid cells (ILCs) can provide early cytokine help against a variety of pathogens in the lungs and gastrointestinal tract. Type 2 ILC (ILC2) are comparable to T helper 2 cells found in the adaptive immune system, which secrete cytokines such as interleukin 5 (IL‐5) and IL‐13 and have been found to play roles in host defense against helminth infections and in allergic responses. Recent studies have identified that programmed cell death protein 1 (PD‐1) and peroxisome proliferator activated receptor‐γ (PPAR‐γ) are highly expressed by ILC2. We examined whether PD‐1 plays a role in ILC2 function and whether there was any connection between PD‐1 and PPAR‐γ Methods: To ensure that only innate immune cells were present, ILC2 cells were examined from RAG1 −/− and PD‐1 −/− xRAG1 −/− mice under steady‐state or following inoculation with IL‐33. We also tested ILC2 generated from bone marrow of RAG1 −/− and PD‐1 −/− xRAG1 −/− mice for their production of cytokines. These in vitro‐derived ILC2 were also exposed to agonist and antagonist of PPAR‐γ. Results: We found that ILC2 from PD‐1 −/− xRAG1 −/− mice had reduced frequencies of IL‐5 and IL‐13 producing cells both in vitro upon IL‐33 stimulation and in vivo following intraperitoneal administration of IL‐33 when compared with ILC2 from RAG1 −/− mice. However, by adding IL‐2, IL‐25, and thymic stromal lymphopoietin to the in vitro cultures, the frequency of IL‐5 and IL‐13 expressing ILC2 from PD‐1 −/− xRAG1 −/− mice became similar to the frequency observed for ILC2 from RAG1 −/− mice. In addition, PPAR‐γ agonists and antagonists were found to increase and decrease PD‐1 expression on ILC2 respectively. Conclusions: These findings illustrate that chronic loss of PD‐1 plays a role in ILC2 function and PD‐1 expression can be modulated by PPAR‐γ.